(untitled) (Altre Modernità, 2019)
This essay examines an indigenous map (1837) of the Missouri and Mississippi river valleys, which offers an alternative to the territorial mappings of US empire in the era of Indian removal. The map was presented by the Ioway delegate Na’hje Ning’e during an intertribal treaty council in Washington in 1837 and depicts the Ioway Nation’s historical occupation of large areas in the Mississippi River Valley. Although the American treaty commissioners ultimately dismissed the map’s historical argument and the Ioway’s claims, its visual presentation of rivers and indigenous migrations routes marked an alternative to US territorial mappings of Indian country. Understanding the Mississippi River Valley as a site of territorial contestation, Na’hjeNing’e’s visual rhetoric took Ioway migrations along these waterways seriously as a basis for indigenous land claims and sovereignty, presenting an alternative to the settler state’s mappings of Native space. At the same time, the imbalance of power relations within American bureaucratic networks meant that the map is an example of disrespected literature: a form of indigenous writing that was legible within colonial settings, but nevertheless disregarded because it did not align with settler-colonial projects of indigenous dispossession. By considering the diplomatic calculations behind it, this essay argues that Na’hjeNing’e’s map asserted a representation of Ioway sovereignty, but also reveals the bounds on that sovereignty at a moment when removal policy and settler expansion profoundly reshaped the social and political place of Indian nations in North America.